CREATION OF STRUCTURAL EMPLOYMENT OPPORTUNITIES IN CRIMPING REGIONS AND THE INTER (NATIONAL) TRADE GAP: A CONCEPTUAL AND EXPERIMENTAL APPROACH - Samplonius-Raut, Shilpa K.; Waalkens, Jan (European Scientific Journal, ESJ, 2013)
Europe 2020 is the EU's strategy to promote the sustainable growth. One of the five ambitious objectives to be reached by 2020 is in the area of employment, whereby it states that 75 % of the population aged 20-64 should be employed. The European Union has provided special attention to the problem related to the crimping regions. The lack of employment opportunities in general and lack structural employment in specific is one of the important characteristics of crimping regions. Among others UWV (Dutch National Employment Office) in its report 2011-12 advises that the regions need to develop a certain economic specialization in order to retain the employment opportunities within the regions. The generation of employment is one of the most important objectives that dictates the policy in the crimping regions. In this paper we explore how this problem can be addressed on the regional level aiming to aid policymakers. The paper concludes with the possible changes in the economic measures to achieve the generation of structural employment in the region. Therefore we firstly provide the rationale of why specialization of regions might help in lifting the burden of the crimp and secondly how taxing of output instead of tax on input such as labour might help to decrease factor costs. As a result of such a decrease the competitive advantage of a region can improve. Thirdly we present an experiment on labour costs with the so called Prohef model introduced by Piet van Elswijk.